Morphological and molecular evidence suggests that Indosasa gigantea and Acidosasa glauca (Poaceae, Bambusoideae, Arundinarieae) are conspecific - Zhengyang Niu; Zhuoyu Cai; Jun Yin; Yihua Tong; Nianhe Xia (PhytoKeys)
Indosasa gigantea is a bamboo with great economical value, but its generic designation has been controversial for a long time. This study aims to ascertain whether I. gigantea belongs to Indosasa or Acidosasa, based on morphological and molecular evidence from both plastome and single-copy nuclear orthologous genes. The results of phylogenetic analyses, based on plastid genomes and nuclear gene sequences, both strongly supported that I. gigantea is distantly related to other members of Indosasa, but clustered with Acidosasa glauca, the type species of Acidosasa. Further morphological studies demonstrated that I. gigantea is conspecific with A. glauca. Thus, I. gigantea was proposed as a synonym of A. glauca. Colour plates as well as a detailed description of this species are also provided.